2021
DOI: 10.1002/elsc.202100086
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the apical growth characteristics of hairy roots using non‐invasive laser speckle contrast imaging

Abstract: Hairy roots are used to produce plant agents and additives. Due to their heterogeneous structure and growth characteristics, it is difficult to determine growthrelated parameters continuously and in real time. Laser speckle contrast analysis is widely used as a non-destructive measurement technique in material testing or in medical technology. This type of analysis is based on the principle that moving objects or particles cause fluctuations in stochastic interference patterns known as speckle patterns. They a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 81 publications
(186 reference statements)
0
2
0
Order By: Relevance
“…The infrared laser points were focused on the dorsal surface of the rats’ hind feet, and the blood perfusion volume of the rats’ skin was measured. Moor FLPI-2 measurement software V2.0 was used to record the data, and V5.0 software was used to process the laser speckle images and data ( 28 ). The final values are the average of both sides.…”
Section: Methodsmentioning
confidence: 99%
“…The infrared laser points were focused on the dorsal surface of the rats’ hind feet, and the blood perfusion volume of the rats’ skin was measured. Moor FLPI-2 measurement software V2.0 was used to record the data, and V5.0 software was used to process the laser speckle images and data ( 28 ). The final values are the average of both sides.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, the potential of biospeckle imaging has been shown in detection of endophytic colonization in leaves ( D’Jonsiles et al., 2020 ). The method has also been used to image bioactivity in the root and apical hairy root tissues ( Braga et al., 2009 ; Ribeiro et al., 2013 ; Schott et al., 2020 ; Schott et al., 2022 ). Figure 1C shows the biospeckle activity in heterogeneous hairy root culture in a cultivation assay over time.…”
Section: Biospeckle Laser Imagingmentioning
confidence: 99%